Company growth and growth opportunities on the example of some EU stock exchanges in the light of market characteristics - Bolek, Monika; Gniadkowska-Szymańska, Agata; Pietraszewski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
This paper analyzes the relationship between growth opportunity measures and the future growth of companies. If there is a correlation between a company’s growth potential and its real growth, then the markets are more predictable and effective. The survey was conducted on the example of the following European markets: Austria, the Baltic Countries, Hungary, France, Poland, and Germany. The goal of this paper is to assess the relationship between growth opportunity measures and the future growth of companies listed on the stock exchanges of some markets in the European Union. The countries considered can be classified according to the size of the state, market liquidity, and the maturity of the exchange. Those external factors were expected to influence the strength of the growth and its opportunity relationship. It was found that growth opportunity measures based on market prices have predicting power for the future growth of companies. They are also strongly related to companies’ future growth in large countries and weakly related to future growth in small countries. This paper adds to the literature on the application of growth opportunity measures regarding market characteristics. These results are in line with the view that market liquidity should increase its efficiency in revealing the value of stocks and the Comprehensive Advantage of Large Countries hypothesis.